ChemInform Abstract: Does Bioelectrochemical Cell Configuration and Anode Potential Affect Biofilm Response?. Issue 18 (11th April 2013) - Kumar, Amit; Katuri, Krishna; Lens, Piet; Leech, Donal
Abstract Review: 41 refs.